2019
DOI: 10.1177/1535370219892846
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory parameters, risk factors predisposing to the development of priapism in sickle cell patients

Abstract: Although sickle cell disease is very common in Oman, priapism is a relatively rare complication of this disease. This study was aimed to identify the clinical and laboratory risk factors that predispose sickle cell disease patients to priapism. In a retrospective, case-control study, data on 21 male sickle cell disease patients, with priapism, were compared to 20 age and sex-matched sickle cell disease patients without priapism from the hospital medical records. Specifically, the demographical, hematological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…A yearly increase as the result of newborn cases is about 120-150 (3). Thus, SCD is a major public health problem in the Sultanate of Oman, with a high rate of morbidity and mortality (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…A yearly increase as the result of newborn cases is about 120-150 (3). Thus, SCD is a major public health problem in the Sultanate of Oman, with a high rate of morbidity and mortality (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…These conflicting studies could be related to differences in various factors such as study design, sickle cell genotype, precipitating factors, genetic factors, effects of intervention, and laboratory methods, all of which can change the hematological values of priapic patients with SCA (8,16,27). In general, the prognostic value of a complete blood count includes other biomarkers (eosinophil, and reticulocyte count), has been associated with the development of acute IP in men with SCA (8,11,13). Furthermore, in this report, patients with priapism > 17.9 hours had a positive correlation for predicting erectile tissue recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the vasculopathy, chronic hemolysis, and veno-occlusive pathogenesis of SCA, multiple hematologic markers are needed to predict the outcome of IP in SCA patients. The role of platelet count (PLT) and mean platelet volume (MPV) in these veno-occlusive mechanisms is well documented (7)(8)(9)(10)(11). Previous studies confirmed the association between IP, defined as a vasculogenic disease, and platelet activation leading to higher MPV (9,10).…”
Section: Original Papermentioning
confidence: 97%
“…[5][6][7][8][9][10] More recently, also retinopathy, priapism, and an increased risk of venous thromboembolism (VTE) were shown to be associated with increased neutrophil counts. [11][12][13][14] Lydian A. de Ligt and Aafke E. Gaartman contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil counts positively correlated with SCD‐related complications such as stroke, acute chest syndrome, and early death 5–10 . More recently, also retinopathy, priapism, and an increased risk of venous thromboembolism (VTE) were shown to be associated with increased neutrophil counts 11–14 …”
Section: Introductionmentioning
confidence: 99%